Temporal Analysis of Andes Virus and Sin Nombre Virus Infections of Syrian Hamsters - Wahl-Jensen, Victoria (American Society for Microbiology, 2007)
Andes virus (ANDV) and Sin Nombre virus (SNV) are rodent-borne hantaviruses that cause a highly lethal hemorrhagic fever in humans known as hantavirus pulmonary syndrome (HPS). There are no vaccines or specific drugs to prevent or treat HPS, and the pathogenesis is not understood. Syrian hamsters infected with ANDV, but not SNV, develop a highly lethal disease that closely resembles HPS in humans. Here, we performed a temporal pathogenesis study comparing ANDV and SNV infections in hamsters. SNV was nonpathogenic and viremia was not detected despite the fact that all animals were infected. ANDV was uniformly lethal with a mean time to death of 11 days. The first pathology detected was lymphocyte apoptosis starting on day 4. Animals were viremic and viral antigen was first observed in multiple organs by days 6 and 8, respectively. Levels of infectious virus in the blood increased 4 to 5 logs between days 6 and 8. Pulmonary edema was first detected ultrastructurally on day 6. Ultrastructural analysis of lung tissues revealed the presence of large inclusion bodies and substantial numbers of vacuoles within infected endothelial cells. Paraendothelial gaps were not observed, suggesting that fluid leakage was transcellular and directly attributable to infecting virus. Taken together, these data imply that HPS treatment strategies aimed at preventing virus replication and dissemination will have the greatest probability of success if administered before the viremic phase; however, because vascular leakage is associated with infected endothelial cells, a therapeutic strategy targeting viral replication might be effective even at later times (e.g., after disease onset).